The Employees Social Security (Amendment) Act 1984 / Aziah Abdul Aziz - Abdul Aziz, Aziah (Faculty of Law, 1985)
The writer's aim in writting this project paper is to study the requirements, benefits and compensations provided under the statutory provisions of the Employees Social Security (Amendment) Act, 1984. The workers who satisfy the requirements and are injured during the course of their employment are eligible for compensation under the provisions of the Act. The Social Security Organisation (SOCSO) is the body which administers and operates the social insurance scheme under the supervision of the Ministry of Labour and Manpower. This project paper also studies the administration of the Social Security Organisation. It also sums up the criticisms and recommendations made by workers and members of the public as regards the working of the Social Security Scheme.